CONSUMER ATTITUDE TOWARDS ADVERTISING ON INSTAGRAM: THE ROLE OF ADS PERSONALIZATION AND CONSUMER EXPERIENCE - Roza, Suswita; Sriayudha, Yayuk; Khalik, Idham; Octavia, Ade (Dinasti Publisher, 2021)
Instagram account users in Indonesia are increasing, in 2020 it was recorded that 69.2 million people have an account on Instagram. For marketers, the increasing number of Instagram account is a market opportunity. It predicts that consumer attitudes and consumer experiences will be influenced by personalized messages in advertisements. The purpose of this study was to analyze the relationship between advertisement personalization, consumer experience, and attitudes towards advertising and brands. The research design is descriptive quantitative with a sample survey method. Research respondents are owners of Instagram accounts in Indonesia, with a total sample of 200 people. The analysis tool uses PLS. From the results of the study, it is known that there is a significant association between the personalization of advertising on Instagram on consumer attitudes of Instagram users towards these advertisements. Research also shows that there is a significant association between consumer experience on consumer attitudes of Instagram users. Furthermore, the study also illustrates a significant association between consumer attitudes of Instagram users towards brand attitudes. It is hoped that the results of this study will contribute empirically to thoughts related to advertising personalization and consumer attitudes towards advertising and brands on social media, particularly through Instagram.